Firm Performance and the Factors That Influence the Adoption of Digital Innovations (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Despite the growing importance of digital innovation—defined as new digital products and services that allow digital transformation of firms across industries, empirical research on digital innovation drivers is still limited, resulting in a knowledge gap. This study looks at how digital capacity and digital orientation affect digital innovation as well as how digital innovation functions as a mediator in the link among digital orientation and digital capability and firm performance. This study centres on IT firms that operate within the ICT sector of India and also utilized a quantitative methodology to evaluate the connections between digital innovation, orientation, capability and firm performance, specifically employing a sample size of 105 SMEs. The findings indicate a noteworthy positive influence of digital capability and digital orientation on digital innovation. Furthermore, it was discovered that digital innovation serves as a mediator in the connection between digital orientation and firm performance as well as between digital capability and firm performance. These results emphasize the significance of cultivating a culture that prioritizes digitalization and enhancing digital competencies in order to stimulate digital innovation, thereby resulting in enhanced financial and non-financial performance for IT firm operating in ICT sector. In order to ensure that the workforce is ready for the digital age, policymakers are urged to fund rescaling programmes and introduce digital education at an early age.